Kodeksowe pozwolenie zintegrowane a sektorowe pozwolenie wodnoprawne - doświadczenia niemieckie: [Codex Integrated Permit and Sectoral Water Permit - German experiences] (Studia Prawnicze / The Legal Studies, 2017)
Problematyka niemieckich aktów administracyjnych służących reglamentacji korzystania ze środowiska była już przedmiotem analizy w literaturze krajowej. Zasadność ponownego jej podjęcia wynika z ewolucji, jakiej na przestrzeni ostatnich dekad doświadczyło niemieckie prawo ochrony środowiska. Jej obrazem jest w szczególności niecodzienna historia podjętego w RFN projektu kodyfikacji tego prawa. Niezwykłość ta ma kilka wymiarów: naukowy, polityczny i pragmatyczny, a dopełnia ją zaskakujący finał, czyli niespodziewana porażka całego przedsięwzięcia po ponad dwudziestu latach żmudnych przygotowań. Jeśli jednak warto o nim wspominać, to dlatego, że wyznacza ono, pomimo końcowego niepowodzenia, godny podziwu standard pracy nad projektem doniosłego aktu prawnego, oparty na konsekwencji i determinacji, wnikliwości i staranności, a przede wszystkim woli współdziałania przedstawicieli nauki, administracji i gospodarki. The author takes the issue of individual administrative acts aimed at rational use of the environment. He is focused on the German experiences. The rationale for this choice is, on one hand, a considerable number of such instruments, provided especially in the water law. On the other hand it is an significant and extensive literature devoted to such instruments. Special role in the development of doctrine played the work on the code of environmental law, which was the central point of an integrated permit. Although there has been no adoption of the Code, but accumulated experiences influence the theory and practice of application of this law. Proof of this is also a history of Water Resources Act, passed in 2009. The need for the adoption of this Act was the result of the consequences of competence changes made to the constitution. These changes were made in order to allow the adoption of the Code. In the new law types of water permits known from previous regulations were repeated, but also there were added selected solutions for environmental integrated protection. That was modeled on the draft Code. It was also added one kind of permission functioning in legislation of federal states.